The Concept of the Creative Individual in Islamic Education: An Analysis of Educational Goals in Human Potential Development from the Perspective of Muhammad Iqbal - Lailatul Jannah; Zainuddin Syarif (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to examine the concept of the objectives of Islamic education in developing human potential from the perspective of Muhammad Iqbal. The background of this research is based on the importance of Islamic education as a means to develop all aspects of human potential, including intellectual, spiritual, and moral dimensions, in the midst of modern challenges. This study employs a qualitative method with a library research approach by analyzing the works of Muhammad Iqbal and relevant literature on Islamic education. The results of the study indicate that, according to Muhammad Iqbal, the objectives of Islamic education are not merely oriented toward the transfer of knowledge, but also toward the formation of a strong “khudi” (selfhood), characterized by independence and creativity. Education should be able to develop intellectual potential, strengthen spirituality, and shape a dynamic and responsible character. Iqbal emphasizes the importance of freedom of thought, creativity, and the active role of individuals in actualizing their potential. Thus, Islamic education, according to Iqbal, plays a strategic role in shaping individuals who are not only knowledgeable but also possess self-awareness and the ability to face the challenges of the modern era.